Li-beta ''aluminum oxide solid electrolyte ceramic and preparation method thereof

By preparing high-stability Na-β" alumina ceramic precursor powder and carrying out high-temperature ion exchange reaction, the problems of the preparation of Li-β" alumina solid electrolyte ceramics in traditional methods are solved, and the preparation of Li-β" alumina solid electrolyte ceramics is achieved with high efficiency and stability.

CN119551967APending Publication Date: 2025-03-04ZHENGZHOU NON FERROUS METALS RES INST CO LTD OF CHALCO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411537224.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The preparation of Li-β" aluminum oxide solid electrolyte ceramics by traditional ion exchange method takes a long time, has a low exchange rate, and is prone to cracking of materials, making it difficult to meet the needs of efficient conversion and structural stability.

Method used

By preparing high stability, high ceramic body density Na-β"alumina ceramic precursor powder, molding and buried sintering treatment, and then ion-exchange reaction with the mixture of lithium oxygen compounds and aluminum oxygen compounds at high temperatures, Li-β"alumina solid electrolyte ceramics were generated.

Benefits of technology

The ion conduction and chemical properties of Li-β" alumina solid electrolyte ceramics are improved, the structural stability is enhanced, the ion exchange time is reduced, and the problem of material cracking is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551967A_ABST
    Figure CN119551967A_ABST
Patent Text Reader

Abstract

The invention relates to Li-beta ''aluminum oxide solid electrolyte ceramic and a preparation method thereof. The method comprises the following steps: obtaining Na-beta'' aluminum oxide ceramic precursor powder; carrying out molding treatment on the Na-beta ''aluminum oxide ceramic precursor powder to obtain a Na-beta'' aluminum oxide ceramic green body; and carrying out buried sintering on the Na-beta ''aluminum oxide ceramic green body to obtain the Na-beta'' aluminum oxide solid electrolyte ceramic, and embedding the Na-beta ''alumina solid electrolyte ceramic into a mixture of a lithium oxide and a first aluminum oxide, and carrying out an ion exchange reaction at a set temperature to obtain the Li-beta'' alumina solid electrolyte ceramic. The preparation method of the Li-beta ''aluminum oxide solid electrolyte ceramic provided by the embodiment of the invention not only can improve the sintered body density of the solid electrolyte ceramic, but also can maintain good stability and excellent ionic conductivity, namely, improve the comprehensive performance of the Li-beta'' aluminum oxide solid electrolyte ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solid electrolyte ceramics, and in particular to a Li-β" alumina solid electrolyte ceramic and a preparation method thereof. Background Art

[0002] Li-β" alumina solid electrolyte ceramics have high Li ion conductivity and can be used in solid-state lithium batteries to promote efficient conversion between electrical energy and chemical energy, which is expected to extend the battery life, conversion rate and safety. This material can be further used in the drive battery of electric vehicles to improve battery energy density, driving range, and reduce charging time.

[0003] At present, Li-β" alumina solid electrolyte ceramics are prepared by ion exchange method, but the traditional ion exchange method for preparing Li-β" alumina solid electrolyte ceramics takes a long time and has a low exchange rate, and the formed Li-β" alumina is very easy to crack. Summary of the invention

[0004] The present application provides a Li-β" alumina solid electrolyte ceramic and a preparation method thereof to solve the following technical problem: how to improve the comprehensive performance of Li-β" alumina solid electrolyte ceramic.

[0005] In a first aspect, the present application provides a method for preparing a Li-β" alumina solid electrolyte ceramic, the method comprising:

[0006] Obtaining Na-β" alumina ceramic precursor powder;

[0007] The Na-β-alumina ceramic precursor powder is subjected to a molding process to obtain a Na-β-alumina ceramic green body;

[0008] The Na-β-alumina ceramic green body is fired to obtain a Na-β-alumina solid electrolyte ceramic;

[0009] The Na-β" alumina solid electrolyte ceramic is buried in a mixture of a lithium oxide compound and a first aluminum oxide compound to perform an ion exchange reaction at a set temperature to obtain a Li-β" alumina solid electrolyte ceramic.

[0010] Optionally, the set temperature is 1400°C to 1500°C.

[0011] Optionally, the ion exchange reaction time is 24h to 36h.

[0012] Optionally, the lithium oxygen compound includes at least one of the following: lithium hydroxide, lithium oxide, lithium aluminate; and / or, the first aluminum oxygen compound includes at least one of the following: aluminum trihydrate, aluminum monohydrate, aluminum oxide.

[0013] Optionally, the weight ratio of the lithium oxide compound to the first aluminum oxide compound is (0.5-1):1.

[0014] Optionally, the burial temperature is 1580°C to 1650°C.

[0015] Optionally, the method of obtaining Na-β" alumina ceramic precursor powder comprises:

[0016] The second aluminum oxide compound, the sodium-containing compound and the stabilizer are heat-treated to obtain a Na-β" alumina ceramic precursor powder; wherein the heat treatment temperature is 1200° C. to 1250° C.; and / or,

[0017] The weight ratio of the second aluminum oxide compound, the sodium-containing compound and the stabilizer is 100:(8-18):(1-3).

[0018] Optionally, the second aluminum oxide compound includes at least one of the following: α aluminum oxide, γ aluminum oxide; and / or,

[0019] The sodium-containing compound includes at least one of the following: anhydrous sodium carbonate, sodium hydroxide, sodium aluminate; and / or the stabilizer includes at least one of the following: lithium-containing oxides, magnesium-containing oxides.

[0020] Optionally, the method further includes:

[0021] The Li-β" alumina solid electrolyte ceramic is washed to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the washing temperature is 50°C to 80°C.

[0022] In a second aspect, the present application provides a Li-β" alumina solid electrolyte ceramic, wherein the Li-β" alumina solid electrolyte ceramic is prepared by any method described in the first aspect.

[0023] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0024] The preparation method of the Li-β" alumina solid electrolyte ceramic provided in an embodiment of the present application comprises: obtaining a Na-β" alumina ceramic precursor powder; subjecting the Na-β" alumina ceramic precursor powder to a molding process to obtain a Na-β" alumina ceramic green body; calcining the Na-β" alumina ceramic green body to obtain a Na-β" alumina solid electrolyte ceramic; burying the Na-β" alumina solid electrolyte ceramic in a mixture of a lithium oxygen compound and a first aluminum oxide compound to perform an ion exchange reaction at a set temperature to obtain a Li-β" alumina solid electrolyte ceramic. A Na-β" alumina ceramic precursor powder with a stable structure and a high β" phase content is subjected to a molding process to obtain a Na-β" alumina ceramic green body with a high density and a uniform structure; the Na-β" alumina ceramic green body is calcined to promote the growth and densification of the crystals of the Na-β" alumina ceramic green body; the Na-β" alumina solid electrolyte ceramic is buried in a mixture of a lithium oxygen compound and a first aluminum oxide compound, and the Na-β" alumina solid electrolyte ceramic and the lithium oxygen compound undergo an ion exchange reaction at a set temperature to generate a Li-β" alumina solid electrolyte ceramic with excellent ion conductivity, while the aluminum oxide compound maintains the structural stability of the Li-β" alumina solid electrolyte ceramic, thereby optimizing the ion conductivity and chemical properties of the Li-β" alumina solid electrolyte ceramic, and the Li-β" alumina solid electrolyte ceramic can maintain good structural stability and excellent ion conductivity, that is, improve the comprehensive performance of the Li-β" alumina solid electrolyte ceramic. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0027] Figure 1 A schematic diagram of a process for preparing a Li-β" alumina solid electrolyte ceramic provided in an embodiment of the present application. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0029] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0030] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following (individuals)" or similar expressions thereof refer to any combination of these items, including any combination of singular (individuals) or plural (individuals). For example, "at least one of a, b, or c", or "at least one of a, b, and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple. "Parts" such as parts by weight and parts by mass indicate the proportional relationship between the components. In the proportional relationship involved in this article, the parameters that need to be described by proportion should be understood as the first term of the proportional formula in the order of description, and the proportional numbers should be understood as the second term of the proportional formula. For example, the weight ratio of substance A, substance B, and substance C is 1:2:3, then substance A, substance B, and substance C should correspond to the proportional numbers in the proportional formula in the order of description, that is, the weight of substance A: the weight of substance B: the weight of substance C = 1:2:3.

[0031] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0032] Li-β" alumina solid electrolyte ceramics have high Li ion conductivity and can be used in solid-state lithium batteries to promote efficient conversion between electrical energy and chemical energy, which is expected to extend the battery life, conversion rate and safety. This material can be further applied to the drive battery of electric vehicles to improve battery energy density, driving range, and reduce charging time. + Relatively small in size, Li +It tends to be inserted into spinel blocks (closely packed non-conductive layers in the β" alumina structure) rather than remain in the conductive plane. Therefore, the preparation of Li-β" alumina solid electrolyte ceramics is difficult. The traditional solid-phase synthesis method synthesizes a spinel structure instead of a layered structure, so it can only be prepared by ion exchange. However, the traditional ion exchange method for preparing Li-β" alumina solid electrolyte ceramics takes a long time and has a low exchange rate, and the formed Li-β" alumina is very easy to crack.

[0033] Therefore, in the first aspect, the present application provides a method for preparing Li-β" alumina solid electrolyte ceramics, Figure 1 A schematic diagram of a process for preparing a Li-β" alumina solid electrolyte ceramic provided in an embodiment of the present application; see Figure 1 , the method comprising:

[0034] S1, obtaining Na-β" alumina ceramic precursor powder;

[0035] In some embodiments, the step of obtaining Na-β" alumina ceramic precursor powder comprises:

[0036] The second aluminum oxide compound, the sodium-containing compound and the stabilizer are heat-treated to obtain a Na-β" alumina ceramic precursor powder; wherein the heat treatment temperature is 1200° C. to 1250° C.; and / or,

[0037] The weight ratio of the second aluminum oxide compound, the sodium-containing compound and the stabilizer is 100:(8-18):(1-3).

[0038] In some embodiments, the second aluminum oxide compound includes at least one of: α aluminum oxide, γ aluminum oxide; and / or

[0039] or,

[0040] The sodium-containing compound comprises at least one of the following: anhydrous sodium carbonate, sodium hydroxide, sodium aluminate; and / or,

[0041] The stabilizer includes at least one of the following: lithium-containing oxides and magnesium-containing oxides.

[0042] In an embodiment of the present application, the raw materials for preparing Na-β" alumina ceramic precursor powder include a second aluminum oxide compound as an aluminum source, a sodium-containing compound as a sodium source, and a stabilizer. The stabilizer can inhibit the transformation of the β" phase to the β' phase in the Na-β" alumina powder during heat treatment, thereby obtaining a Na-β" alumina ceramic precursor powder with a high β" phase content and structural stability at high temperatures. The temperature of the above-mentioned heat treatment can be 1200℃~1250℃, so that the second aluminum oxide compound, the sodium-containing compound and the stabilizer can chemically react to fully generate Na-β" alumina ceramic precursor powder. Exemplarily, the temperature of the above-mentioned heat treatment can be 1200℃, 1210℃, 1220℃, 1230℃, 1240℃, 1250℃, etc.

[0043] The weight ratio of the second aluminum oxide compound, the sodium-containing compound and the stabilizer can be 100:(8-18):(1-3), so as to obtain high-quality Na-β" alumina ceramic precursor powder, ensuring that the synthesized Na-β" alumina powder has less impurities, high β" phase content and maintains structural stability at high temperatures. Exemplarily, the weight ratio of the second aluminum oxide compound, the sodium-containing compound and the stabilizer can be 100:8:1, 100:15:2, 100:18:3, 100:12:2, 100:14:3, etc.

[0044] The above-mentioned second aluminum oxide compound can be a combination of one or more of α-alumina and γ-alumina. Generally speaking, in order to ensure the purity of the product, a high-purity (purity ≥99.99, Fe≤30ppm) aluminum oxide compound can be selected; the above-mentioned sodium-containing compound can be a combination of one or more of anhydrous sodium carbonate, sodium hydroxide, and sodium aluminate; the above-mentioned stabilizer can be a combination of one or more of lithium oxide and magnesium oxide.

[0045] Exemplarily, as an embodiment of S1, it includes: mixing a high-purity aluminum oxide compound, a sodium-containing compound and a stabilizer to obtain a mixed material; and sequentially performing post-treatment (wet homogenization grinding, drying and crushing) and heat treatment (high-temperature solid phase synthesis) on the mixed material to obtain a Na-β" alumina ceramic precursor powder.

[0046] S2, forming the Na-β-alumina ceramic precursor powder to obtain a Na-β-alumina ceramic green body;

[0047] In an embodiment of the present application, Na-β" alumina ceramic precursor powder is subjected to a molding process to obtain a Na-β" alumina ceramic green body having a high density and a uniform structure. Exemplarily, the molding may include: first pre-molding the Na-β" alumina ceramic precursor powder at a uniaxial pressure of 15 to 20 MPa, and then performing secondary compaction molding at an isostatic pressure of 100 to 300 MPa.

[0048] S3, calcining the Na-β-alumina ceramic green body to obtain a Na-β-alumina solid electrolyte ceramic;

[0049] In some embodiments, the calcination temperature is 1580°C to 1650°C.

[0050] In the embodiments of the present application, buried firing is a special process operation during the material sintering process, that is, a method of burying the material to be sintered under a specific medium for sintering. The purposes of buried firing include: isolating the air, increasing pressure, reducing the loss of element volatilization, and creating a special atmosphere. On the one hand, buried firing can provide a uniform heating environment: during the buried firing process, the ceramic green body is buried in a specific powder material. These buried powders can make the green body receive more uniform heat in various parts during the heating process, avoiding defects such as cracks and deformation of the ceramic due to local overheating or overcooling. On the other hand, it can prevent oxidation and pollution: buried powder can isolate the outside air to a certain extent, reduce the chance of the green body contacting oxygen at high temperature, and thus prevent the occurrence of oxidation reaction. At the same time, it can also avoid contamination by other impurities to ensure the purity of the ceramic. The Na-β" alumina ceramic green body is buried to promote the growth and densification of the crystals of the Na-β" alumina ceramic green body. The burying temperature can be 1580℃~1650℃, so that the Na-β" alumina ceramic green body can be fully sintered and dense, and the crystal structure is gradually improved, so as to obtain Na-β" alumina solid electrolyte ceramics with good properties (mechanical properties and ionic conductivity). Exemplarily, the above-mentioned burying temperature can be 1580℃, 1590℃, 1600℃, 1610℃, 1620℃, 1630℃, 1640℃, 1650℃, etc. In addition, the burying powder used in the burying can be the above-mentioned Na-β" alumina ceramic precursor powder.

[0051] S4. The Na-β-alumina solid electrolyte ceramic is buried in a mixture of a lithium oxide compound and a first aluminum oxide compound to perform an ion exchange reaction at a set temperature to obtain a Li-β-alumina solid electrolyte ceramic.

[0052] In some embodiments, the set temperature is 1400°C to 1500°C.

[0053] In some embodiments, the ion exchange reaction time is 24 hours to 36 hours.

[0054] In an embodiment of the present application, Na-β" alumina solid electrolyte ceramic is buried in a mixture of a lithium oxide compound and a first aluminum oxide compound, and under set temperature conditions, the Na-β" alumina solid electrolyte ceramic and the lithium oxide compound undergo an ion exchange reaction to generate a Li-β" alumina solid electrolyte ceramic with excellent ion conductivity. At the same time, the first aluminum oxide compound maintains the structural stability of the Li-β" alumina solid electrolyte ceramic, thereby optimizing the ion conductivity and chemical properties of the Li-β" alumina solid electrolyte ceramic, and thus the Li-β" alumina solid electrolyte ceramic can maintain good structural stability and excellent ion conductivity. The above-mentioned set temperature can be 1400°C to 1500°C, so that the Na-β" alumina solid electrolyte ceramic and the lithium oxygen compound undergo an ion exchange reaction, optimize the crystal structure of the Li-β" alumina solid electrolyte ceramic, and improve the structural stability and ion conductivity of the Li-β" alumina solid electrolyte ceramic. Exemplarily, the above-mentioned set temperature can be 1400°C, 1410°C, 1420°C, 1430°C, 1440°C, 1450°C, 1460°C, 1470°C, 1480°C, 1490°C, 1500°C, etc. The time of the ion exchange reaction can be 24h to 36h, so that the Na-β" alumina solid electrolyte ceramic and the lithium oxygen compound undergo an ion exchange reaction. Exemplarily, the time of the ion exchange reaction can be 24h, 25h, 26h, 27h, 28h, 29h, 30h, 31h, 32h, 33h, 34h, 35h, 36h, etc.

[0055] In some embodiments, the lithium oxygen compound includes at least one of the following: lithium hydroxide, lithium oxide, lithium aluminate; and / or,

[0056] The first aluminum oxide compound includes at least one of the following: aluminum trihydrate, aluminum monohydrate, and aluminum oxide.

[0057] In the embodiment of the present application, the lithium oxygen compound may be a combination of one or more of lithium hydroxide, lithium oxide, and lithium aluminate; the first aluminum oxygen compound may be a combination of one or more of aluminum trihydrate, aluminum monohydrate, and aluminum oxide.

[0058] In some embodiments, the weight ratio of the lithium oxygen compound to the first aluminum oxygen compound is (0.5-1):1.

[0059] In an embodiment of the present application, the weight ratio of the lithium oxygen compound to the first aluminum oxide compound can be (0.5-1):1, which fully improves the degree of ion exchange between the Na-β" alumina solid electrolyte ceramic and the lithium oxygen compound, optimizes the crystal structure of the Li-β" alumina solid electrolyte ceramic, and improves the structural stability and ion conductivity of the Li-β" alumina solid electrolyte ceramic. Exemplarily, the weight ratio of the above-mentioned lithium oxygen compound to the first aluminum oxide compound is 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc.

[0060] In some embodiments, the method further comprises:

[0061] The Li-β" alumina solid electrolyte ceramic is washed to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the washing temperature is 50°C to 80°C.

[0062] In an embodiment of the present application, the Li-β" alumina solid electrolyte ceramic is washed to improve the purity of the Li-β" alumina solid electrolyte ceramic. The washing temperature can be 50°C to 80°C, thereby improving the washing efficiency, making it easier to remove adsorbents and pollutants on the surface of the Li-β" alumina solid electrolyte ceramic, improving the ion transfer efficiency of the Li-β" alumina solid electrolyte ceramic, and improving the chemical stability and mechanical stability of the Li-β" alumina solid electrolyte ceramic during use. Exemplarily, the washing temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0063] In summary, the preparation method of a Li-β" alumina solid electrolyte ceramic provided in the embodiment of the present application has the following advantages:

[0064] 1. Prepare Na-β" alumina ceramic precursor powder to provide the raw material basis for subsequent molding and sintering. Precursor powder with stable structure and high β" phase content can ensure the performance of the final ceramic product. The stable structure helps to maintain the stability of the ceramic in the subsequent process, and the high β" phase content is conducive to improving the ion conductivity;

[0065] 2. Molding to obtain Na-β" alumina ceramic green body, converting the powder into a green body with a specific shape and size, in preparation for subsequent sintering and ion exchange reactions. Through a specific molding method, a green body with high density and uniform structure can be obtained. Higher density is conducive to reducing the pores in the ceramic and improving its mechanical strength and stability; the uniform structure can ensure that the performance of each part of the ceramic is consistent during the subsequent heat treatment process;

[0066] 3. Buried firing can obtain Na-β" alumina solid electrolyte ceramics, promote the crystal growth and densification of ceramic green body, and improve the performance of ceramics. Buried firing can provide a uniform heating environment to prevent the green body from reacting adversely with the external atmosphere at high temperature. At the same time, it can also control the sintering atmosphere, which is conducive to the growth and densification of crystals. After buried firing, Na-β" alumina solid electrolyte ceramics have higher density, better crystal structure and higher ionic conductivity;

[0067] 4. Li-β" alumina solid electrolyte ceramics are obtained by ion exchange reaction. Through ion exchange reaction, Na-β" alumina solid electrolyte ceramics are converted into Li-β" alumina solid electrolyte ceramics with excellent ion conductivity, while maintaining the structural stability of the ceramics. Lithium ions have a small ion radius and a high ion mobility. By exchanging with sodium ions, the ion conductivity of the ceramics can be significantly improved, and the presence of aluminum oxide compounds can maintain the structural stability of the ceramics and prevent the destruction of the ceramic structure during the ion exchange process. The Li-β" alumina solid electrolyte ceramics obtained in this way have both excellent ion conductivity and good structural stability, thereby improving its comprehensive performance.

[0068] Therefore, the above preparation method provides an effective way to produce high-performance solid electrolyte ceramics, and can obtain Li-β" alumina solid electrolyte ceramics with good structural stability and excellent ion conductivity, meeting the demand for high-performance electrolyte materials in the fields of solid-state batteries and the like.

[0069] In a second aspect, the present application provides a Li-β" alumina solid electrolyte ceramic, wherein the Li-β" alumina solid electrolyte ceramic is prepared by any method described in the first aspect.

[0070] The Li-β" alumina solid electrolyte ceramic is realized based on the preparation method of the above-mentioned Li-β" alumina solid electrolyte ceramic. The specific steps of the preparation method of the Li-β" alumina solid electrolyte ceramic can refer to the above-mentioned embodiment. Since the Li-β" alumina solid electrolyte ceramic adopts part or all of the technical solutions of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment, which will not be repeated here one by one.

[0071] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for the unrecorded specific conditions in the following examples are usually measured according to national standards. If there is no corresponding national standard, then carry out according to general international standards, normal conditions or according to the conditions recommended by the manufacturer.

[0072] Example 1

[0073] A method for preparing Li-β" alumina solid electrolyte ceramics, specifically comprising:

[0074] High-purity α-alumina, sodium aluminate and lithium hydroxide are mixed, and the mixed material is then wet-mixed and homogenized for 10 hours, and then dried, crushed and heat-treated (high-temperature solid-phase synthesis) to obtain Na-β" alumina ceramic precursor powder; wherein the weight ratio of high-purity α-alumina, sodium aluminate and lithium hydroxide is 100:14:2, the heat treatment temperature is 1250°C, and the heat preservation is 2 hours;

[0075] The Na-β" alumina ceramic precursor powder is firstly formed by uniaxial pressure at 15MPa, and then isostatically pressed at 100MPa to obtain a Na-β" alumina ceramic green body;

[0076] The Na-β" alumina ceramic green body is calcined, and the Na-β" alumina ceramic precursor powder is used as calcined powder to obtain the Na-β" alumina solid electrolyte ceramic; wherein the calcination temperature is 1600°C;

[0077] The Na-β-alumina solid electrolyte ceramic is buried in a mixture of lithium aluminate and alumina powder to perform an ion exchange reaction at a set temperature to obtain a Li-β-alumina solid electrolyte ceramic; wherein the set temperature is 1400° C., the ion exchange reaction time is 24 hours, and the weight ratio of lithium aluminate to alumina powder is 1:1;

[0078] The Li-β" alumina solid electrolyte ceramic is washed with water to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the water washing temperature is 80°C.

[0079] Example 2

[0080] A method for preparing Li-β" alumina solid electrolyte ceramics, specifically comprising:

[0081] High-purity α-alumina, anhydrous sodium carbonate and magnesium oxide are mixed, and the mixed material is then wet-mixed and homogenized for 10 hours, and then dried, crushed and heat-treated (high-temperature solid-phase synthesis) to obtain Na-β" alumina ceramic precursor powder; wherein the weight ratio of high-purity α-alumina, anhydrous sodium carbonate and magnesium oxide is 100:18:1, the heat treatment temperature is 1250°C, and the heat preservation is 2 hours;

[0082] The Na-β" alumina ceramic precursor powder is firstly formed by uniaxial pressure at 15MPa, and then isostatically pressed at 200MPa to obtain a Na-β" alumina ceramic green body;

[0083] The Na-β" alumina ceramic green body is calcined, and the Na-β" alumina ceramic precursor powder is used as calcined powder to obtain the Na-β" alumina solid electrolyte ceramic; wherein the calcination temperature is 1650°C;

[0084] The Na-β-alumina solid electrolyte ceramic is buried in a mixture of lithium hydroxide and alumina powder to perform an ion exchange reaction at a set temperature to obtain a Li-β-alumina solid electrolyte ceramic; wherein the set temperature is 1400° C., the ion exchange reaction time is 36 hours, and the weight ratio of lithium aluminate to alumina powder is 1:1;

[0085] The Li-β" alumina solid electrolyte ceramic is washed with water to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the water washing temperature is 80°C.

[0086] Example 3

[0087] A method for preparing Li-β" alumina solid electrolyte ceramics, specifically comprising:

[0088] High-purity γ-alumina, sodium hydroxide and magnesium hydroxide are mixed, and the mixed material is wet-mixed and homogenized for 10 hours, and then dried, crushed and heat-treated (high-temperature solid-phase synthesis) to obtain Na-β" alumina ceramic precursor powder; wherein the weight ratio of high-purity γ-alumina, sodium hydroxide and magnesium hydroxide is 100:8:2, the heat treatment temperature is 1200°C, and the heat preservation is 2 hours;

[0089] The Na-β" alumina ceramic precursor powder is firstly formed by uniaxial pressure at 15MPa, and then isostatically pressed at 200MPa to obtain a Na-β" alumina ceramic green body;

[0090] The Na-β" alumina ceramic green body is calcined, and the Na-β" alumina ceramic precursor powder is used as calcined powder to obtain the Na-β" alumina solid electrolyte ceramic; wherein the calcination temperature is 1580°C;

[0091] The Na-β-alumina solid electrolyte ceramic is buried in a mixture of lithium hydroxide and alumina powder to perform an ion exchange reaction at a set temperature to obtain a Li-β-alumina solid electrolyte ceramic; wherein the set temperature is 1450° C., the ion exchange reaction time is 36 hours, and the weight ratio of lithium hydroxide to alumina powder is 0.5:1;

[0092] The Li-β" alumina solid electrolyte ceramic is washed with water to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the water washing temperature is 80°C.

[0093] Example 4

[0094] A method for preparing Li-β" alumina solid electrolyte ceramics, specifically comprising:

[0095] High-purity γ-alumina, sodium hydroxide and magnesium hydroxide are mixed, and the mixed material is then wet-mixed and homogenized for 10 hours, and then dried, crushed and heat-treated (high-temperature solid-phase synthesis) to obtain Na-β" alumina ceramic precursor powder; wherein the weight ratio of high-purity γ-alumina, sodium hydroxide and magnesium hydroxide is 100:12:3, the heat treatment temperature is 1230°C, and the temperature is kept for 2 hours;

[0096] The Na-β" alumina ceramic precursor powder is firstly formed by uniaxial pressure at 15MPa, and then isostatically pressed at 200MPa to obtain a Na-β" alumina ceramic green body;

[0097] The Na-β" alumina ceramic green body is calcined, and the Na-β" alumina ceramic precursor powder is used as calcined powder to obtain the Na-β" alumina solid electrolyte ceramic; wherein the calcination temperature is 1620°C;

[0098] The Na-β-alumina solid electrolyte ceramic is buried in a mixture of lithium hydroxide and alumina powder to perform an ion exchange reaction at a set temperature to obtain a Li-β-alumina solid electrolyte ceramic; wherein the set temperature is 1500° C., the ion exchange reaction time is 30 hours, and the weight ratio of lithium hydroxide to alumina powder is 0.8:1;

[0099] The Li-β" alumina solid electrolyte ceramic is washed with water to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the water washing temperature is 80°C.

[0100] Comparative Example 1

[0101] A method for preparing Li-β" alumina solid electrolyte ceramics, specifically comprising:

[0102] High-purity α-alumina, sodium aluminate and lithium hydroxide are mixed, and the mixed material is then wet-mixed and homogenized for 10 hours, and then dried, crushed and heat-treated (high-temperature solid-phase synthesis) to obtain Na-β" alumina ceramic precursor powder; wherein the weight ratio of high-purity α-alumina, sodium aluminate and lithium hydroxide is 100:10:2, the heat treatment temperature is 1100°C, and the heat preservation is 2 hours;

[0103] The Na-β" alumina ceramic precursor powder is firstly formed by uniaxial pressure at 15MPa, and then isostatically pressed at 100MPa to obtain a Na-β" alumina ceramic green body;

[0104] The Na-β" alumina ceramic green body is calcined, and the Na-β" alumina ceramic precursor powder is used as calcined powder to obtain the Na-β" alumina solid electrolyte ceramic; wherein the calcination temperature is 1600°C;

[0105] The Na-β-alumina solid electrolyte ceramic is buried in a mixture of lithium aluminate and alumina powder to perform an ion exchange reaction at a set temperature to obtain a Li-β-alumina solid electrolyte ceramic; wherein the set temperature is 1200° C., the ion exchange reaction time is 24 hours, and the weight ratio of lithium aluminate to alumina powder is 1:1;

[0106] The Li-β" alumina solid electrolyte ceramic is washed with water to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the water washing temperature is 80°C.

[0107] Comparative Example 2

[0108] A method for preparing Li-β" alumina solid electrolyte ceramics, specifically comprising:

[0109] High-purity α-alumina, sodium aluminate and lithium hydroxide are mixed, and the mixed material is then wet-mixed and homogenized for 10 hours, and then dried, crushed and heat-treated (high-temperature solid-phase synthesis) to obtain Na-β" alumina ceramic precursor powder; wherein the weight ratio of high-purity α-alumina, sodium aluminate and lithium hydroxide is 100:14:2, the heat treatment temperature is 1250°C, and the heat preservation is 2 hours;

[0110] The Na-β" alumina ceramic precursor powder is firstly formed by uniaxial pressure at 15MPa, and then isostatically pressed at 100MPa to obtain a Na-β" alumina ceramic green body;

[0111] The Na-β" alumina ceramic green body is calcined, and the Na-β" alumina ceramic precursor powder is used as calcined powder to obtain the Na-β" alumina solid electrolyte ceramic; wherein the calcination temperature is 1600°C;

[0112] The Na-β" alumina solid electrolyte ceramic is buried in a mixture of lithium aluminate and alumina powder to perform an ion exchange reaction at a set temperature to obtain a Li-β" alumina solid electrolyte ceramic; wherein the set temperature is 1400° C., the ion exchange reaction time is 24 hours, and the weight ratio of lithium aluminate to alumina powder is 0.3:1;

[0113] The Li-β" alumina solid electrolyte ceramic is washed with water to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the water washing temperature is 80°C.

[0114] The Na-β" alumina powder β" phase, Na-β" alumina solid electrolyte ceramic green body density, ceramic body density, and Li-β" alumina solid electrolyte ceramic ion exchange rate, ion conductivity and other performance indicators of Examples 1 to 4 and Comparative Examples 1 to 2 were tested. Please refer to the performance indicators of Li-β" alumina solid electrolyte ceramics shown in Table 1.

[0115] Table 1 Performance indicators of Li-β" alumina solid electrolyte ceramics

[0116]

[0117] In Table 1, body density refers to volume density, which is the ratio of the dry mass of an object to its total volume (the sum of the volumes of solids, open pores and closed pores), that is, the mass per unit volume.

[0118] It can be seen from Table 1 that according to the analysis of Examples 1 to 4 and Comparative Examples 1 to 2, the Li-β" alumina solid electrolyte ceramics provided in the embodiments of the present application have obvious advantages in both ion exchange rate and ion conductivity.

[0119] ≥80%, ionic conductivity at 1×10 -4 S cm -1 The above can be effectively applied to solid-state lithium batteries as solid electrolyte materials.

[0120] One or more technical solutions in the embodiments of the present application also have at least the following technical effects or advantages:

[0121] (1) The embodiment of the present application first prepares Na-β" alumina solid electrolyte ceramics with high stability and high ceramic body density to provide a precursor for preparing Li-β" alumina solid electrolyte ceramics; secondly, the traditional ion exchange method is to immerse the Na-β" alumina solid electrolyte ceramics in molten Li molten salt at 600-900°C for more than 72 hours for ion exchange. Due to the low exchange temperature and long time, the exchanged Li-β" alumina solid electrolyte ceramics are prone to low exchange rate and poor structural stability, resulting in ceramic cracking. The embodiment of the present application uses saturated Li vapor at high temperature for gas phase ion exchange, which ensures the ion exchange rate of the Li-β" alumina solid electrolyte ceramics while ensuring the structural stability of the ceramics, making it difficult to crack;

[0122] (2) The preparation method of the Li-β" alumina solid electrolyte ceramic provided in the embodiment of the present application, the prepared Li-β" alumina solid electrolyte ceramic has a high ion exchange rate, reduces the ion exchange time, and the Li-β" alumina solid electrolyte ceramic after exchange has stable mechanical properties and excellent ion conductivity;

[0123] (3) The preparation method of the Li-β" alumina solid electrolyte ceramic provided in the embodiment of the present application can not only improve the sintered body density of the solid electrolyte ceramic, but also maintain good stability and excellent ionic conductivity.

[0124] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A method for preparing a Li-β-alumina solid electrolyte ceramic, the method comprising: Obtaining Na-β" alumina ceramic precursor powder; The Na-β-alumina ceramic precursor powder is subjected to a molding process to obtain a Na-β-alumina ceramic green body; The Na-β-alumina ceramic green body is fired to obtain a Na-β-alumina solid electrolyte ceramic; The Na-β" alumina solid electrolyte ceramic is buried in a mixture of a lithium oxide compound and a first aluminum oxide compound to perform an ion exchange reaction at a set temperature to obtain a Li-β" alumina solid electrolyte ceramic.

2. The method according to claim 1, characterized in that The set temperature is 1400°C to 1500°C.

3. The method according to claim 1 or 2, characterized in that: The ion exchange reaction time is 24h to 36h.

4. The method according to claim 1, characterized in that: The lithium oxygen compound comprises at least one of the following: lithium hydroxide, lithium oxide, lithium aluminate; and / or, The first aluminum oxide compound includes at least one of the following: aluminum trihydrate, aluminum monohydrate, and aluminum oxide.

5. The method according to claim 1 or 4, characterized in that: The weight ratio of the lithium oxide compound to the first aluminum oxide compound is (0.5-1):

1.

6. The method according to claim 1, characterized in that The burial temperature is 1580°C to 1650°C.

7. The method according to claim 1, characterized in that The method for obtaining the Na-β" alumina ceramic precursor powder comprises: The second aluminum oxide compound, the sodium-containing compound and the stabilizer are heat-treated to obtain a Na-β" alumina ceramic precursor powder; wherein the heat treatment temperature is 1200° C. to 1250° C.; and / or, The weight ratio of the second aluminum oxide compound, the sodium-containing compound and the stabilizer is 100:(8-18):(1-3).

8. The method according to claim 7, characterized in that The second aluminum oxide compound comprises at least one of: α aluminum oxide, γ aluminum oxide; and / or The sodium-containing compound comprises at least one of the following: anhydrous sodium carbonate, sodium hydroxide, sodium aluminate; and / or, The stabilizer includes at least one of the following: lithium-containing oxides and magnesium-containing oxides.

9. The method according to claim 1, characterized in that: The method further comprises: The Li-β" alumina solid electrolyte ceramic is washed to obtain a Li-β" alumina solid electrolyte ceramic product; wherein the washing temperature is 50°C to 80°C.

10. A Li-β" alumina solid electrolyte ceramic, characterized in that: The Li-β" alumina solid electrolyte ceramic is prepared by the method described in any one of claims 1 to 9.